Pengaruh Komunikasi, Kerjasama Tim Dan Gaya Kepemimpinan Terhadap Kinerja Perangkat Desa (Studi Kasus Pada Kantor Desa Negororejo, Kecamatan Lumbang, Kabupaten Probolinggo) - Ida Ristianah; Siti Asiyah; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to find out, test, and explain the effect of communication, teamwork, and leadership style on the performance of village officals, this research is a type of quantitive research the mothod used is multiple linear analysis. The sampling technique for all village officals totalling 44 samples. To solve the problem this study using SPSS with the help of validity test, reliability test, normality test, multicollineritas test, multiple lener analysis, heteroscedaksity test, f test dan t test. The result of this study indicate that simultaneesously the variable of communication, teamwork, and leadership stayle have a significant effect on the performance of village officials, and there is a partial influence between the influence of communication, teamwork, and leadership style. Keyword : Comuniccation (X1), Teamwork (X2), and Leadership style (X3) on employe performance (Y)